2020
DOI: 10.1016/j.amepre.2020.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Discrimination and Mental Distress Amid the COVID-19 Pandemic: Evidence From the Understanding America Study

Abstract: Introduction: This study examines COVID-19−associated discrimination regardless of infection status. It evaluates the contribution of various risk factors (e.g., race/ethnicity and wearing a face mask) and the relationship with mental distress among U.S. adults in March and April 2020, when the pandemic escalated across the country. Methods: Participants consisted of a probability-based, nationally representative sample of U.S. residents aged ≥18 years who completed COVID-19−related surveys online in March and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
143
6
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(172 citation statements)
references
References 33 publications
13
143
6
2
Order By: Relevance
“…There are also numerous factors not controlled for in this study that could have contributed to participant self-reported discrimination, including exposure to social media and differences in shelter-in-place orders across regions. 11,26 While the current study did not show an increase in mental distress associated with self-reported racial/ethnic discrimination due to COVID-19 among Asian subgroups, previous studies have shown that Asians are less likely to report anxiety and depression because of stigma attached to mental disorders. [27][28][29] Despite the fact that an increase in anxiety and depression was not shown in this study, future studies should further explore the possible implications of COVID-19 discrimination on health and wellness using instruments that are sensitive in Asian populations.…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…There are also numerous factors not controlled for in this study that could have contributed to participant self-reported discrimination, including exposure to social media and differences in shelter-in-place orders across regions. 11,26 While the current study did not show an increase in mental distress associated with self-reported racial/ethnic discrimination due to COVID-19 among Asian subgroups, previous studies have shown that Asians are less likely to report anxiety and depression because of stigma attached to mental disorders. [27][28][29] Despite the fact that an increase in anxiety and depression was not shown in this study, future studies should further explore the possible implications of COVID-19 discrimination on health and wellness using instruments that are sensitive in Asian populations.…”
Section: Discussioncontrasting
confidence: 84%
“…11 Chinese, Korean, Japanese, Vietnamese, and Other API groups in the current study all experienced increased self-reported racial/ethnic discrimination due to COVID-19 than the rates previously reported for Asian Americans overall. 11 Additionally, while the current study found that certain Asian American subgroups reported high concerns for physical assault (up to 46% in Vietnamese Americans), previous studies have found that only 26% of Asian Americans overall feared someone might threaten or physically attack them. 2 These prior studies 2,11 did not disaggregate by Asian ethnic subgroups, masking any possible differences in experiences between them.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…Another avenue of future research concerns the role of perceived discrimination: in an American study, Blacks and Asians show an increase in perceived discrimination during the pandemic, which was associated with higher mental distress (Liu et al 2020). Since we operationalize risk perception as domain-specific worries, a more unstable mental state may be reflected in changed risk perceptions.…”
Section: Discussionmentioning
confidence: 99%
“…On top of the common difficulties from the pandemic such as financial crisis, social isolation, and fear of disease, Asian populations in the U.S. have been experiencing an added layer of hardships since the beginning of the current pandemic [ 10 ]. As the first COVID-19 cases reported in the U.S. between January and February 2020 were identified from travelers arriving from China and their household contacts [ 11 ], Chinese and other East Asians were often seen as the origin and spreaders of the COVID-19 disease [ 12 ].…”
Section: Introductionmentioning
confidence: 99%